RESEARCH OF TECHNICAL CHARACTERISTICS OF COAL SORBENT GS-1. - Оrtiqov Nosir Tojimurodovich; Abdulahat Djalilov Turapovich; Karimov Mas’ud Ubaydulla O’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Carbon sorbent GS-1 from cation exchanger KU-2-8. KU-2-8 was soaked in a 6% hydrochloric acid solution and dried at a temperature from 110°C to 120°C. The dried product was cooled to room temperature and placed in a muffle furnace for heat treatment in an inert atmosphere, the process was carried out at a rate of temperature increase from 40°C to 500°C, kept at 500°C for 2 hours, and cooled to room temperature in an inert atmosphere. Cleaning of dust and resins on the surface of the obtained sorbent, i.e., the activation process, was carried out in an inert atmosphere at a temperature of 550–650 °C in the presence of water vapor.